Utilization of Sandblasting Waste as an Alternative Material for Paving Blocks - Rezasyah Alifiadi; Agus Slamet (Jurnal Multidisiplin Madani, 2022)
Sandblasting is an activity of cleaning industrial equipment made of metal using quartz sand. Every day the amount of waste produced is getting bigger so it needs to be processed to reduce its surface area. One way that can be used to process sandblasting waste is solidification into building material products. This study uses sandblasting waste as a substitute for fine aggregate in the manufacture of paving blocks. Paving block production was carried out using three research variables, namely the weight ratio of cement and waste, cement water factor (FAS), and maximum grain size. Comparison of the weight of cement and waste using  composition of 1:3, 1:4, and 1:5. The cement water factor used was 0.35, 0.425, and 0.5. While the grain sizes that were filtered were 1.2 mm, 2.4 mm, and 4.75 mm. The results showed that of the 27 variations of the mixture produced, the samples with sample code V5 (composition 1:3, FAS 0.425, and grain size 2.4 mm) produced the highest compressive strength, namely 25 MPa with quality B. ANOVA analysis was performed to determine the effect of the three variables on compressive strength and it was found that the weight ratio composition of cement and waste was the most influential. The TCLP test was carried out to determine the potential for leaching of heavy metals Cr6+, Cu, Pb, and Zn, which then resulted in the content of the four substances being below the quality standard of Government Regulation Number 22 of 2021